Potensi PLTS Hybrid di PT. Makmur Indah Selaras International Muaro Jambi - Suprapto, Eko; Djufri, S. Umar; Hendi, Hendi (Journal of Electrical Power Control and Automation (JEPCA), 2023)
Renewable energy that is suitable for the tropical climate in Indonesia with an average solar radiation of 4.8 kwh/m2 per day is the use of photovoltaics or solar cells. To use solar cells, they can be placed on the roof of a building to save existing land, such as at PT. Makmur Indah Selaras International. The research method uses direct observation and literature study to obtain data on the use of solar panels at the factory. Meanwhile, the aim of this research was to see the utilization of existing PLTS with a hybrid system at PT. Makmur Indah Selaras Internasional, which is one of the palm oil factories operating in Muaro Regency, Jambi.